Impact of Organizational Citizenship Behaviour on Customer Satisfaction - Yunus Yildiz; Hastyar Hiwa Hama Amin (Eurasian Journal of Management & Social Sciences, 2020)
The aim of this study is to find out the impact of organizational citizenship behaviour on customer satisfaction. For this reason, data have been collected from 150 small-medium enterprises in Sulaimani and Erbil cities of the Kurdistan Region of Iraq. The data have been evaluated by using covariance, correlation and regression analysis. It has been seen that organizational citizenship behaviours of employees have a strong effect on customer satisfaction. Also, the dimensions of organizational citizenship behaviour (Altruism, Conscientiousness, Sportsmanship, Civic virtue, Respect, and Reverence) have positive and meaningful impacts on customer satisfaction. The significance of this finding reveals that increasing the citizenship behaviours of employees in small-medium enterprises are positively associated with customer satisfaction.